2016
DOI: 10.18632/oncotarget.9698
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation-mediated silencing of microRNAs contributes to HPV-induced anchorage independence

Abstract: Cervical cancer and a subset of anogenital and head-and-neck carcinomas are caused by high-risk types of the human papillomavirus (hrHPV). During hrHPV-induced malignant transformation keratinocytes become able to grow anchorage independently, a tumorigenic trait at least partly associated with inactivation of tumor suppressor genes. We used hrHPV-containing keratinocytes to investigate the role of DNA methylation-mediated silencing of microRNAs (miRNAs) in the acquisition of anchorage independence.Anchorage d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 74 publications
4
37
0
Order By: Relevance
“…In cervical cancer, DNA methylation-mediated silencing of a rapidly growing number of coding and non-coding genes has been identified and their functional relevance has been demonstrated (32). Increased methylation has been demonstrated for a number of miRNAs, including miR-34b, miR-95, miR-124 and miR-375 (32). The present study found that miR-144 expression was also repressed, indicating that DNA methylation-mediated silencing of miR-144 may exist in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In cervical cancer, DNA methylation-mediated silencing of a rapidly growing number of coding and non-coding genes has been identified and their functional relevance has been demonstrated (32). Increased methylation has been demonstrated for a number of miRNAs, including miR-34b, miR-95, miR-124 and miR-375 (32). The present study found that miR-144 expression was also repressed, indicating that DNA methylation-mediated silencing of miR-144 may exist in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Copy number changes, mRNA, and miRNA expression were determined in all four cell lines at six to eight different passages (time points) ( Table 1). As described previously, the selected time points represent distinct stages in HPV-induced transformation ( Figure 1a) [16]. Table 1.…”
Section: Anchorage Independence Coincides With Marked Molecular Changesmentioning
confidence: 99%
“…Table 1. Passage numbers included for all four HPV-transformed cell lines [16]. FK16A FK16B FK18A FK18B T1 p18 p21 p19 p17 T2 p22 p22 p21 p18 T3 p39 p45 p47 p40 T4 p52 p51 p60 p52 T5 p109 p89 p92 p90 T6 p115 p102 p99 p98 T7 p206 p140 p148 p146 T8 p222 p169 p160 p164 FK16A and FK16B contain HPV16, whereas FK18A and FK18B contain HPV18.…”
Section: Anchorage Independence Coincides With Marked Molecular Changesmentioning
confidence: 99%
See 2 more Smart Citations